Scaling behaviour of a multiply connected fluctuating interface in two dimensions - Ayşe, Erzan; Hüseyin, Kaya; Alkan, Kabakçioğlu (World Scientific Pub Co Pte Ltd, 2002)
We consider a one-parameter kinetic model for a fluctuating interface which can be thought of as an infinite string decorated with infinitely many closed strings. Numerical simulations show that a number of scaling exponents describing this string system may be related to the Kardar-Parisi-Zhang exponents. However, as the average velocity of the infinite string is taken to zero, and the string system becomes an isotropic fractal set, we also find new exponents which cannot be reduced to previously known ones.
Keywords: Dynamic lattice systems (kinetic Ising, etc.) and systems on graphs in time-dependent statistical mechanics